The phospholipase D pathway mediates the inflammatory response of the retinal pigment epithelium - Mateos, Melina Valeria (2014)
The retinal pigment epithelium (RPE) plays an important immunological role in the retina and it is involved in many ocular inflammatory diseases that may end in loss of vision and blindness. In this work the role of phospholipase D (PLD) classical isoforms, PLD1 and PLD2, in the inflammatory response of human RPE cells (ARPE-19) was studied. ARPE-19 cells exposed to lipopolysaccharide (LPS, 10 µg/ml) displayed increased levels of NO production and diminished mitochondrial function after 48 h of incubation. Furthermore, 24 h LPS treatment strongly induced cyclooxygenase-2 (COX-2) expression and activation of extracellular signal-regulated kinase (ERK1/2). EGFP-PLDs showed the typical subcellular localization, perinuclear for PLD1 and plasma membrane for PLD2. LPS increased PLD activity by 90% with respect to the control. The presence of PLD1 inhibitor (EVJ 0.15 µM) or PLD2 inhibitor (APV 0.5 µM) reduced LPS-induced COX-2 induction but only PLD2 inhibition reduced ERK1/2 activation. Mitochondrial function was restored after inhibition of PLD2 and ERK1/2. These findings evidence the participation of PLD2 as a promoter of RPE inflammatory response through ERK1/2 and COX-2 regulation. Our results demonstrate for the first time distinctive roles of PLD isoforms in pathological conditions in RPE.